Neonatal screening of hearing function by otoacustic emissions: A single center experience - Živić Ljubica; Obradović Slobodan; Stojanović Stevan; Zbiljić Ivana; Jakovljević Vladimir Lj.; Živić Danijela; Stojanović Jasmina; Laban Olivera (Vojnosanitetski Pregled)
Background/Aim. Nowadays development of techniques enables detection of hearing impairment in a very short time, immediately after birth by using otoacoustic emissions. They are low-pitched sounds produced in physiologically clear cochlea and can be recorded in cochlear outer meatus. By this method, complete data are found on a whole presynaptic auditory nervous system functioning that has mostly been affected by pathological changes making it a perfect screening test. Reliability and sensibility of this method is up to 98%. The aim of this study was to present the first results of systematic neonatal screening of hearing function by otoacoustic emissions in the Clinical Center Kragujevac (Kragujevac, Serbia). Methods. This prospective study of neonatal hearing screening function, initiated systematically by the 2008 at the Clinical Center Kragujevac, included full-term newborns and premature born ones, within the first 24 h after birth, using a DPOAEs interacoustics otoread-screener. Retesting was done after a month. Results. From January 1st, 2009 to December 1st, 2010, a total number of examined infants by this method was 1,994 out of which 1,778 were full-term and 216 were premature born. The test passing was higher in the group of full-term babies (92.5%) than in the preterm ones (55.1%). No bilateral answers were recorded in premature born children compared to the full-term ones, of whom a larger number was with missing lateral responses. The results of re-examination test in the group of full-term born and premature newborns were 83.7%, and 61%, respectively. Conclusion. Deliberately provoked transient otoacoustic emission is an efficient method in testing hearing function in newborns, since it is non-invasive, rapid and objective. Its correlation with audibly evoked potentials is very high, which confirms its reliability.